Association of NCF2, NCF4, and CYBA Gene Polymorphisms with Rheumatoid Arthritis in a Chinese Population - Tian-Ping Zhang; Rui Li; Qian Huang; Han-Feng Pan; Dong-Qing Ye; Xiao-Mei Li (Journal of Immunology Research)
Objective. Recent studies have focused on the special roles of NADPH-oxidase in multiple autoimmune diseases. Nevertheless, the association of genetic variation in NADPH-oxidase genes with rheumatoid arthritis (RA) was not extensively studied in a Chinese population. We performed this study to examine the association of NCF2, NCF4, and CYBA gene polymorphisms with RA susceptibility in a Chinese population. Methods. Six single nucleotide polymorphisms (SNPs) (NCF2 rs10911363, NCF4 rs1883112, rs4821544, rs729749, CYBA rs3794624, and rs4673) were genotyped in a cohort composed of 593 RA patients and 596 normal controls. Improved multiple ligase detection reaction (iMLDR) was used for genotyping. Results. We observed that NCF4 rs4821544 CT genotype and C allele frequencies in RA patients were significantly decreased when compared to controls (CT vs. TT: P=0.043; C vs. T: P=0.031), and rs4821544 polymorphism was significantly associated with an increased RA risk under the dominant model (TT vs. CT+CC: P=0.031). Our results also indicated that rs729749 CT genotype frequency was significantly lower in RA patients than that in controls (CT vs. CC: P=0.033). Moreover, the rs729749 CT genotype frequency was also significantly decreased in RA patients in males (CT vs. CC: P=0.024). No significant association between NCF2 and CYBA gene polymorphisms and RA susceptibility was observed. There were significant associations between rs4821544 TT genotype and T allele frequencies and anti-CCP in male RA patients. Conclusions. In summary, NCF4 rs4821544 and rs729749 polymorphisms might contribute to RA susceptibility, while NCF2 and CYBA gene polymorphisms were not associated with RA susceptibility.